Revision of five species of Euonymus (Celastraceae) from East and South Asia - Cheng, Du; Yunjuan, Zuo; Lei, Wu; Quanru, Liu; Ma, Jinshuang (Phytotaxa, 2015)
Based on re-collections at known sites, field observations, study of specimens and review of literature, taxonomic revisions of five Euonymus species from East and South Asia are presented, including three new synonyms of Euonymus laxiflorus Champion ex Bentham, a new synonym of Euonymus mengtzeanus (Loesener) Sprague, a new synonym of Euonymus gracillimus Hemsley, and supplemental descriptions of the floral features of Euonymus pittosporoides Cheng ex Ma and Euonymus ficoides Cheng ex Ma. Lectotypes are also designated for seven names wherein the holotype had not been designated in the original publication. Additionally, the conservation status of these species is reevaluated according to IUCN standards (version 3.1).